Reproductive Autonomy, Family Planning Attitudes and Affecting Factors in Married Women of Reproductive Age - Berna Bayır; Aslıhan Turan; Merve Yazar Renkyorgancı (Ebelik ve Sağlık Bilimleri Dergisi)
Objective: The aim of this study was to determine reproductive autonomy, family planning attitudes and influencing factors of married women of reproductive age.Methods: A cross-sectional study was conducted with 344 women in Turkey between May and September 2024. Participants completed a sociodemographic form, the Reproductive Autonomy Scale, and the International Family Planning Attitude Scale. The data obtained were analysed using SPSS 25 software. Descriptive statistics and multiple linear regression analysis were used to evaluate the data. Statistical significance was assessed at the p